The Relationship Between Analytical Thinking and Intelligence Quotient with PAI Learning Outcomes in State Elementary Schools in Tarumajaya District, Regency, Bekasi - Latifah, Nur; Khoir, Abdul; Annuri (Proceeding International Conference on Education, 2023)
This study aims to determine the relationship between the ability to think analytically and the intelligence quotient partially and together with the learning outcomes of PAI students in public elementary schools in Tarumajaya District, Kab. Bekasi. This research uses quantitative methods with correlation research types. This study used random sampling with a sample of 320 students from a population of 1539 students taken from grade 5 in public elementary schools in Tarumajaya District. The results of this study indicate that the research hypothesis is proven to have a value of Py12 > 0, which explains that there is a positive relationship between analytical thinking ability (X1) and intelligence quotient (X2) together with Islamic education learning outcomes of students (Y) at the public elementary school level in Tarumajaya District, Kab. Bekasi.